Development of cantaloupe (Cucumis melo) pulp powder using foam-mat drying method: Effects of drying conditions on microstructural of mat and physicochemical properties of powder. Issue 15 (18th November 2017) - Salahi, Mohammad Reza; Mohebbi, Mohebbat; Taghizadeh, Masoud
ABSTRACT: In this study, the effects of drying conditions on moisture content, water activity ( a w ), dissolution time, solubility, hygroscopicity, β-carotene, color, glass transition temperature ( T g ), and sticky point temperature ( T s ) of foam-mat-dried cantaloupe pulp powders and microstructure of dried cantaloupe pulp foams were investigated. Drying was performed in three temperatures (40, 55, and 70°C) on 3- and 5-mm thicknesses. The analysis of scanning electron microscopy micrographs with grey-level co-occurrence matrix showed that there is wide porous structure of dried foams at higher speeds drying. The temperature increase reduced moisture content and a w, and increased hygroscopicity, and thickness rise increased moisture content and a w and consequently decreased powders' hygroscopicity under the same thickness and drying temperature, respectively. Increase in drying temperature would increase the reconstitution speed of powders into water and therefore the dissolution time decreased. In addition, results showed that the powder produced at 40°C have higher β-carotene content than those of produced at 55 and 70°C. With increasing drying temperature from 40 to 70°C, Lightness parameter ( L ) was increased while redness parameter ( a ) was decreased. The T g and T s were compared by plotting them in a graph against moisture content. For all drying processes the T s was higher than the T g . The drying conditions at 70°C (higher drying temperature) and 3 mm (lower thickness) led to a shorter drying time and consequent lower energy demand to produce a powdered cantaloupe pulp with high stability (low moisture content, a w, and high T g and T s ) and reconstitution speed of powder into water.